Trade-off Analysis in Strengthening the Criteria for Master Teacher Promotion - Julius Garzon; Marvin Daguplo; Leomarich Casinillo; Melbert Hungo (Universidade Estadual de Alagoas, 2024)
Effective master teachers constitute a valuable human resource playing a significant role not only as instructional leaders but also as educational researchers. However, the pressing demands of quality education alongside changing policies call for the need to ensure that these leaders meet competitive standards. Using the developmental-evaluative design, this study which is anchored on Criterion Theory, aims to enhance the existing criteria of the Department of Education (DepEd) in screening, selecting, and hiring Master Teacher applicants. Delphi technique and trade-offs analysis with ten expert respondents derived nine new and consensually evaluated measures (research training, research conference, publication, INSET/LAC, completed researches, best practices/innovations, qualifying examination, master's degree & awards) comprising the "Enhanced Criteria for Master Teacher Promotion" at 70-point cut-off qualification. The discriminant function model constituted data from 60 Master Teachers in the Maasin City Division and confirmed discriminatory success at 91.78% variability during model validation of 15 Master Teachers. Thus, the new criteria demonstrate the potential to assure the DepEd of competent and quality instructional leaders that the country needs today. This study recommends the adoption of the enhanced criteria as a policy. However, further evaluation is necessary to strengthen its validity before its full implementation.